A facile method for the preparation of black TiO2 by Al reduction of TiO2 and their visible light photocatalytic activity. Issue 57 (21st September 2020) - Li, Jun; Wu, En-Hui; Hou, Jing; Huang, Ping; Xu, Zhong; Jiang, Yan; Liu, Qian-Shu; Zhong, Yu-Quan
Abstract : Black TiO2 has attracted widespread attention due to its visible light absorption and wide range of applications. Abstract : Black TiO2 has attracted widespread attention due to its visible light absorption and wide range of applications. However, the currently reported preparation methods for black TiO2 are not suitable for large-scale production due to its being prepared under high vacuum and over a long time. We have successfully prepared black TiO2 under normal pressure and short time conditions. The as-prepared black titanium dioxide was characterized by XRD, XPS, TEM, UV-visible absorption spectrum and other characterization methods. The result shows that the as prepared black titanium dioxide had a disordered structure and oxygen vacancy defects on the surface, and exhibits excellent visible and near infrared absorption performance. The black TiO2 sample was prepared under 650 °C 60 min exhibits excellent visible light photocatalytic performance, and can degrade 56% MO after visible light irradiation for 120 min.